EFEKTIVITAS MEDIA SPORT MATH ADVENTURE TERHADAP PENINGKATAN KEBUGARAN JASMANI DAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Husni Gutomo, Wahid; Ngabiyanto; Avrilianda, Decky; Widiarti, Nuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the potential of the Sport Math Adventure program—which integrates physical activity with mathematical problem-solving—to improve the physical fitness and critical thinking skills of elementary school students through a systematic literature review. The study employed a Systematic Literature Review (SLR) following the PRISMA guidelines. The search was conducted on Google Scholar, PubMed, ERIC, and Semantic Scholar, covering publications from 2021 to 2026. Of the 512 identified articles, 24 met the inclusion criteria and were analyzed thematically. The findings indicate that integrating physical activity into academic learning consistently improves students’ physical fitness and cognitive performance. Moderate- to vigorous-intensity physical activity combined with cognitive tasks yields significant positive effects on mathematical ability. Elements of adventure and physical-mathematical challenges have the potential to serve as the foundation for an effective Sport Math Adventure media design to improve both physical fitness and critical thinking skills among elementary school students.